'These are Our Beans': Learning by Doing, Innovation and Resilience in Old Havana's Escuela Taller. (1st April 2019) - Gilblom, Elizabeth A.
Abstract : This qualitative study explores the perceptions and experiences of 18 current students and graduates of Escuela Taller 'Gaspar de Melchor de Jovellanos', a two-year cultural heritage restoration programme located in Old Havana, Cuba. The researcher investigated the participants' perceptions and experiences of 'Aprender Haciendo', the pedagogical approach of Escuelas Taller that combines theory with practice. Additionally, students and graduates described the challenges they faced while learning how to restore cultural heritage and they provided the ways in which they overcome these barriers. Specifically, innovation and resilience are used to overcome the lack and cost of resources. Finally, Escuelas Taller as a formal community-based learning programme is discussed.